![sin(\frac{\pi }{4}-8x)=-\frac{\sqrt3}{2}\\\\\frac{\pi }{4}-8x=(-1)^{n}\cdot (-\frac{\pi }{3})+\pi n=(-1)^{n+1}\cdot \frac{\pi}{3}+\pi n\; ,\; n\in Z\\\\8x=\frac{\pi }{4}-(-1)^{n+1}\cdot \frac{\pi }{3}-\pi n\\\\x=\frac{\pi }{32}+(-1)^{n+2}\cdot \frac{\pi}{24}-\frac{\pi n}{8}\; ,\; n\in Z sin(\frac{\pi }{4}-8x)=-\frac{\sqrt3}{2}\\\\\frac{\pi }{4}-8x=(-1)^{n}\cdot (-\frac{\pi }{3})+\pi n=(-1)^{n+1}\cdot \frac{\pi}{3}+\pi n\; ,\; n\in Z\\\\8x=\frac{\pi }{4}-(-1)^{n+1}\cdot \frac{\pi }{3}-\pi n\\\\x=\frac{\pi }{32}+(-1)^{n+2}\cdot \frac{\pi}{24}-\frac{\pi n}{8}\; ,\; n\in Z](https://tex.z-dn.net/?f=sin%28%5Cfrac%7B%5Cpi%20%7D%7B4%7D-8x%29%3D-%5Cfrac%7B%5Csqrt3%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7B%5Cpi%20%7D%7B4%7D-8x%3D%28-1%29%5E%7Bn%7D%5Ccdot%20%28-%5Cfrac%7B%5Cpi%20%7D%7B3%7D%29%2B%5Cpi%20n%3D%28-1%29%5E%7Bn%2B1%7D%5Ccdot%20%5Cfrac%7B%5Cpi%7D%7B3%7D%2B%5Cpi%20n%5C%3B%20%2C%5C%3B%20n%5Cin%20Z%5C%5C%5C%5C8x%3D%5Cfrac%7B%5Cpi%20%7D%7B4%7D-%28-1%29%5E%7Bn%2B1%7D%5Ccdot%20%5Cfrac%7B%5Cpi%20%7D%7B3%7D-%5Cpi%20n%5C%5C%5C%5Cx%3D%5Cfrac%7B%5Cpi%20%7D%7B32%7D%2B%28-1%29%5E%7Bn%2B2%7D%5Ccdot%20%5Cfrac%7B%5Cpi%7D%7B24%7D-%5Cfrac%7B%5Cpi%20n%7D%7B8%7D%5C%3B%20%2C%5C%3B%20n%5Cin%20Z)
0\; ,\\\\sinx=\frac{a-1}{a+3}\; \; ,\; \; a\ne -3\; ,\\\\-1\leq \frac{a-1}{a+3}\leq 1\; \; \Rightarrow \; \; \left \{ {{\frac{a-1}{a+3}\leq 1} \atop {\frac{a-1}{a+3}\geq -1}} \right. \; \; \left \{ {{\frac{a-1-a-3}{a+3}\leq 0} \atop {\frac{a-1+a+3}{a+3}\geq 0}} \right. \; \left \{ {{\frac{-2}{a+3}\leq 0} \atop {\frac{2(a+1)}{a+3}\geq 0}} \right. \\\\\left \{ {{a+3\geq 0} \atop {a\in (-\infty ,-3)\cup (-1,+\infty )}} \right. \; \left \{ {{a\geq 0\; \; ,\; \; a>0} \atop {a\in (-\infty ,-3)\cup (-1,+\infty )}} \right. \; \Rightarrow \; \; a\in (0,+\infty )" alt="2)\; \; (a+3)\cdot sinx=a-1\; ,\; \; a>0\; ,\\\\sinx=\frac{a-1}{a+3}\; \; ,\; \; a\ne -3\; ,\\\\-1\leq \frac{a-1}{a+3}\leq 1\; \; \Rightarrow \; \; \left \{ {{\frac{a-1}{a+3}\leq 1} \atop {\frac{a-1}{a+3}\geq -1}} \right. \; \; \left \{ {{\frac{a-1-a-3}{a+3}\leq 0} \atop {\frac{a-1+a+3}{a+3}\geq 0}} \right. \; \left \{ {{\frac{-2}{a+3}\leq 0} \atop {\frac{2(a+1)}{a+3}\geq 0}} \right. \\\\\left \{ {{a+3\geq 0} \atop {a\in (-\infty ,-3)\cup (-1,+\infty )}} \right. \; \left \{ {{a\geq 0\; \; ,\; \; a>0} \atop {a\in (-\infty ,-3)\cup (-1,+\infty )}} \right. \; \Rightarrow \; \; a\in (0,+\infty )" align="absmiddle" class="latex-formula">